Social Support For Coping Mechanism in Diabetic Ulcer Patients : A Cross Sectional Study - Ikhsan, Muhammad; Rauzatul Jannah, Syarifah; Hermansyah, Hermansyah; Syarif, Hilman; Hayati, Wirda (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background: Diabetic ulcers are complications that often occur in patients with Diabetes Mellitus and will have an impact on the sufferer's physical, psychological, social and economic. One thing that is really needed by patients to help heal is social support from their surroundings. Objective: to examine the relationship of social support with coping mechanisms in ulcer patients. Method: using an analytical survey with a cross-sectional study, the sampling method used is purposive sampling of 116 respondents. The instruments used in this study were the Coping Scale Questionnaire (CSQ) to measure coping mechanisms and the Multidimensional Scale of Perceived Social Support to measure social support. Result and Discussion: The results of this study were found in the coping mechanism and social support variables, the majority had adaptive coping and high social support as many as 79 respondents (68.1%). It can be concluded from 79 respondents with high support, there are 61 respondents (77.2%) with adaptive coping mechanisms and of 37 respondents with low social support, 19 respondents (51.4%) with maladaptive coping mechanisms. Hypothesis test results obtained P value = 0.004<0.05. Conclusions: there is a significant relationship between social support and coping mechanisms in diabetic ulcer patients.